The contribution of board of directors’ competency, commitment, integrity, and accountability to the timely submission of the annual financial report of agricultural co-operative societies in the state of Perak and the moderating effect of office support and document handling / Hatta Haji Sapwan - Haji Sapwan, Hatta (2014)
The post-mortem on the National Co-operative Policy 2002-2010 had highlighted, among others, the following weaknesses: low entrepreneurship skills, lack of understanding among members of co-operatives, and lack of professional management. In 1999, 58.8% (97 out of 165) agricultural co-operatives in Perak failed to submit their audited financial report on time as required by the Co-operative Society Act 1993 (Act 503) and Regulations. The targeted key performance indicators (KPI) for the Core Strategic V of National Cooperative Policy 2011 - 2020 requires that at least 90% of the co-operatives have audited annual financial report and 90% of the co-operatives conduct the Annual General Meeting (AGM). This study, which involves the Agricultural Co-operative Societies in Perak, aims to examine the relationship between educational level and training attained with the competency of BODs in ensuring timely submission of financial reporting. A series of tests were carried out to determine the relationship of BODs’ competency, commitment, integrity and accountability with timely submission of financial reporting. Additionally, the study attempts to find out whether organizational support and document handling system moderate the relationship between independent and dependent variables. The findings of the study reveal that there is a relationship between educational level and training attained with BODs’ competency. There are evidences that show only commitment, integrity and accountability have a relationship with timely submission of financial reporting. There are also findings that indicate the existence of a congruent relationship between commitment, integrity and accountability of BODs, with office support and document handling which serve as moderators. Therefore, establishing appropriate level of commitment, integrity and accountability with sufficient office support and proper document handling system is pertinent to timely submission of financial reporting.